The Economics of Clove Farming in Indonesia - World Bank Group (World Bank, Washington, DC, 2017)
This report aims to inform the current debate over the taxation of kreteks in Indonesia by examining clove-farming livelihoods. It presents results from a comprehensive, household-level, economically-focused survey of 600 clove farmers across the two largest clove-growing regions, Sulawesi and Central Java. The survey examines the role that clove farming plays in these households’ economic lives, among other related topics.